The Impact of Motivation on Employee Retention: Organizational Citizenship Behavior as a Mediator and Communication as a Moderator - Nurfitri Kurniawati; Asri Laksmi Riani (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of motivation and communication on employee retention in educational institutions, with organizational citizenship behavior (OCB) serving as a mediating variable. Data were collected via questionnaires from employees across various educational institutions and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that motivation has a positive and significant impact on both employee retention and OCB. Communication also plays a crucial role in enhancing employee retention and, notably, has a significant effect on OCB. OCB was found to be a significant mediator in the relationship between motivation and employee retention. However, the moderating effects of communication on the relationships between motivation and OCB, as well as between OCB and employee retention, were not significant. These findings highlight the importance of boosting employee motivation through career development programs and reward systems, alongside open and transparent communication, to foster OCB and improve retention within educational institutions. This study offers both theoretical and practical contributions to understanding the mechanisms underlying employee retention in the education sector.